2013
DOI: 10.1007/s00540-013-1748-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of interscalene block technique on adverse hemodynamic events

Abstract: Ultrasound-guided ISB permits the use of a low volume of local anesthetic and seems to reduce the incidence of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These findings are in contrast to those of Liu et al [17] and Taboada et al [16] who found no differences in the abovementioned categories between their study groups. Gianesello et al [7] also found similar block onset times in their study groups, but their patients received ultrasound-guided IBPBs with 20 mL of 0.5% levobupivacaine HCl and PNS-confirmed IBPBs with 40 mL of 0.5% levobupivacaine HCl.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings are in contrast to those of Liu et al [17] and Taboada et al [16] who found no differences in the abovementioned categories between their study groups. Gianesello et al [7] also found similar block onset times in their study groups, but their patients received ultrasound-guided IBPBs with 20 mL of 0.5% levobupivacaine HCl and PNS-confirmed IBPBs with 40 mL of 0.5% levobupivacaine HCl.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, the possibility of continuously observing the end of the needle and visualizing the spread of a local anaesthetic (LA) on a monitor can enhance the safety and efficacy of blocks. Some studies have shown that the possibility of reduction of LA dose was higher with an ultrasound-guided technique rather than a neurostimulation-guided technique [6,7]. Moreover, the reduction of complications like intravascular injections of cardiotoxic and neurotoxic LAs or brachial plexopathy becomes possible because of the availability of Doppler-color visualization during IBPB; this is not possible using a PNS-confirmed technique [8,9].…”
mentioning
confidence: 99%
“…Gianesello et al [31] compared ultrasound-guided IBPB with 20 mL or 40 mL of 0.5% with neurostimulation for rotator cuff repairs, and recorded the need for antihypertensive drug. They found that three patients of group NS required urapidil administration because of hypertension and concluded that ultrasound-guided IPBP permitted the use of a low volume of local anaesthetic and seemed to reduce the incidence of hypertension.…”
Section: Motor Block Terminationmentioning
confidence: 99%
“…The introduction of ultrasound visualisation has revolutionised regional anaesthesia (RA) due to the possibility of observing the end of the needle and visualising the spread of local anaesthetic (LA) on the monitor. Moreover, it allows one to reduce the dose of LA [1], shortens the time of the onset of RA [2], minimises the rate of failed blocks [3] and the occurrence of brachial plexopathy [4], as well as the frequency of other unwelcome adverse events, such as intravascular injections of cardio-or neurotoxic LA [5], and diaphragm paralysis [6,7] with respiratory disorder [8]. In the end, IPBP produces appropriate analgesia for the postoperative period compared with general anaesthesia, which improves patients' satisfaction [9,10].…”
mentioning
confidence: 99%